A Study On Academic Staff’s Perceptions Of Internationalisation Of The Curriculum In University Of Technology And Applied Science, Salalah - Kathiri, Ali Mohammed Fael Hubais Al (2023)
The internationalisation of the curriculum (IoC) has been a significant trend in higher education across the globe. However, there is a dearth of empirical studies on this area of research in the Arab countries, including the Omani higher education context. Thus, this study was conducted to explore academic staff’s perceptions of curriculum internationalisation at: institutional, departmental and course levels at University of Technology and Applied Science (UTAS-Salalah), Salalah, Oman. Additionally, the study investigated how academic staff’s perceptions of curriculum internationalisation differ according to their years of experience in higher education, years of experience at UTAS-Salalah, and departments. The study also tried to explore academic staff’s perceptions of the three core levels of curriculum internationalisation (awareness, competence, and expertise) at UTAS-Salalah and identify challenges that academic staff encounter in the internationalisation of the curriculum at UTAS-Salalah. The two-phased explanatory sequential mixed-methods design was utilized to answer five research questions addressed by the study. Both quantitative and qualitative data were collected. While the quantitative data were collected using an adapted questionnaire, the qualitative data were collected through semi-structured interviews. The samples of the study included 267 academic lecturers in the quantitative phase and nine academic staff for the semi-structured interviews. The quantitative data were analysed using descriptive statistics and one-way ANOVA in SPSS, whereas the qualitative data were analysed using thematic analysis